2023
DOI: 10.1155/2023/5581492
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Need for Online Social Feedback (NfOSF) Scale

Abstract: People are known to adjust their behavior based on social information. Starting from 2004, social media rapidly became a new social arena for human interaction, and scholars widely studied the effect of likes on people’s psyche and behavior. However, likes are just one of the possible social feedbacks among many others on social media. Moreover, social feedback influence should be analyzed recognizing individual differences in people’s needs and desires for them. This work was aimed at developing and validatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 128 publications
0
22
0
Order By: Relevance
“…The findings substantiated the hypothesis and are in agreement with existing research such as Wang et al [63], who note that entertainment significantly affects community engagement. Duradoni et al [83] highlight the positive impact of social media usage on fostering healthy behaviors and secure relationships within the Italian community. Their work culminates in the successful validation of the Italian Social Media Engagement Questionnaire, a tool specifically designed to investigate the patterns and dynamics of social media engagement among Italian speakers.…”
Section: Social Interaction As a Contributingmentioning
confidence: 99%
“…The findings substantiated the hypothesis and are in agreement with existing research such as Wang et al [63], who note that entertainment significantly affects community engagement. Duradoni et al [83] highlight the positive impact of social media usage on fostering healthy behaviors and secure relationships within the Italian community. Their work culminates in the successful validation of the Italian Social Media Engagement Questionnaire, a tool specifically designed to investigate the patterns and dynamics of social media engagement among Italian speakers.…”
Section: Social Interaction As a Contributingmentioning
confidence: 99%
“…Jonason and Krause (2013) observed that narcissism correlates with decreased affective empathy and difficulties in emotion recognition. However, more recent studies suggest that whereas narcissism negatively impacts affective empathy, it might be positively linked with cognitive empathy (Turner et al, 2019;Doyle, 2020;Wertag et al, 2021;Duradoni et al, 2023). One contributing factor to these inconsistencies is measurement methods, which range from self-report assessments to behavioral tasks.…”
Section: Empathy and Narcissismmentioning
confidence: 99%
“…As of the latest data, SM platforms collectively boast billions of users worldwide, underscoring their influence and reach. Popular features of SM include instant messaging, content sharing, networking, and community engagement, which have become integral to modern marketing strategies, especially in the luxury sector [7].…”
Section: Introductionmentioning
confidence: 99%